Bio-morphological properties of Ferula tadshikorum Pimenov and Ferula foetida (Bunge) Regel under plantation conditions - Halkuzieva, Mokhira A; Khamraeva, Dilovar T; Bussmann, Rainer W (Plant Science Today, 2023)
Ferula foetida (Bunge) Regel and Ferula tadshikorum Pimenov are widely used in folk medicine and in the pharmaceutical industry. As a result of their use in the pharmaceutical industry, their populations are widely declining. This article presents the bio-morphological characteristics of Ferula foetida and Ferula tadshikorum under plantation conditions. In 2014-2021, plantations of Ferula foetida and Ferula tadshikorum were established on 20 hectares of arable land in Arnasay district, Jizzakh region, Uzbekistan. In February, March, April, and May 2018-2020, the growth dynamics, size of leaves and the morpho-biological classification of roots of 2 to 6-year-old Ferula foetida and Ferula tadshikorum were studied under plantation conditions. In the second year, both species had 2 whole normal leaves and from the third to the sixth-year different numbers of leaves were developed depending on the age of the plant and the remains of last year's leaf petiole were maintained at the base of the plant. The shape and color of the roots differed, with Ferula tadshikorum roots being cylindrical, dark brown and Ferula foetida barrel-shaped and light liver-colored. All experiments were carried out in arable and conditionally irrigated areas characterized by relatively low rainfall and gray and gray-grass-type soils. During the 1st to 6th year of growth of Ferula tadshikorum and Ferula foetida specific features of their bio-morphological characteristics under new growth conditions were studied and it was found that they could be planted in unirrigated areas.